Effects of cognitive-motor dual-task training combined with auditory motor synchronization training on cognitive functioning in individuals with chronic stroke: A pilot randomized controlled trial. Issue 22 (June 2018) - Park, Myoung-Ok; Lee, Sang-Heon
Abstract: Background: Preservation and enhancement of cognitive function are essential for the restoration of functional abilities and independence following stroke. While cognitive-motor dual-task training (CMDT) has been utilized in rehabilitation settings, many patients with stroke experience impairments in cognitive function that can interfere with dual-task performance. In the present study, we investigated the effects of CMDT combined with auditory motor synchronization training (AMST) utilizing rhythmic cues on cognitive function in patients with stroke. Methods: The present randomized controlled trial was conducted at a single rehabilitation hospital. Thirty patients with chronic stroke were randomly divided an experimental group (n = 15) and a control group (n = 15). The experimental group received 3 CMDT + AMST sessions per week for 6 weeks, whereas the control group received CMDT only 3 times per week for 6 weeks. Changes in cognitive function were evaluated using the trail making test (TMT), digit span test (DST), and stroop test (ST). Results: Significant differences in TMT-A and B ( P  = .001, P  = .001), DST-forward ( P  = .001, P  = .001), DST-backward ( P  = .000, P  = .001), ST-word ( P  = .001, P  = .001), and ST-color ( P  = .002, P  = .001) scores were observed in both the control and experimental groups, respectively. Significant differences in TMT-A ( P  = .001), DST-forward ( P  = .027), DST-backward ( P  = .002), and ST-word ( P  = .025) scores were observed between the 2 groups. Performance speed on the TMT-A was faster in the CMDT + AMST group than in the CMDT group. Moreover, DST-forward and DST-backward scores were higher in the CMDT + AMST group than in the CDMT group. Although ST-color results were similar in the 2 groups, ST-word scores were higher in the CMDT + AMST group than in the CMDT group. Conclusion: This finding indicates that the combined therapy CMDT and AMST can be used to increase attention, memory, and executive function for people with stroke.